Analisis dan Perancangan Website untuk Peningkatan Pemasaran UMKM di Agrowisata Nanas Desa Tangkit Baru Jambi - Novitasari Novitasari; Noneng Marthiawati; Kevin Kurniawansyah; Hetty Rohayani (Router : Jurnal Teknik Informatika dan Terapan, 2026)
The development of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize digital media as an effective marketing tool. The Pineapple Agrotourism area in Tangkit Baru Village, Jambi, has significant economic potential through various pineapple-based products; however, conventional marketing practices have limited the reach of product promotion. This study aims to analyze requirements and design a website as a digital marketing medium to improve the visibility and marketing reach of MSMEs in the Pineapple Agrotourism area of Tangkit Baru Village, Jambi. The research method consisted of the requirements, design, development, testing, deployment, and review and feedback stages. Data were collected through observation, interviews, and literature studies. The results indicate that the designed website includes key features such as a homepage, agrotourism information, an e-commerce dashboard, a product catalog, a shopping cart, and educational content pages. The proposed website is expected to support MSME digital transformation, enhance the competitiveness of local products, and expand digital-based marketing reach.